Concordance between Clinical Diagnosis and Medicare Claims of Depression among Older Primary Care Patients - Hwang, Seungyoung (Am J Geriatr Psychiatry, 2014)
OBJECTIVE: To identify patient characteristics associated with concordance of Medicare claims with clinically identified depression. DESIGN: Cohort of 742 older primary care patients linked to Medicare claims data. MEASUREMENTS: Structured Clinical Interview for DSM-IV major depressive disorder (MDD) and clinically-significant minor depression. RESULTS: Among 474 patients with depression, 198 patients had a Medicare claim for depression (sensitivity: 42%, 95% confidence interval (CI) 37% to 46%). Among 268 patients who did not meet criteria for depression, 235 patients did not have a Medicare claim for depression (specificity: 88%, 95% CI 83% to 91%). After adjustment for demographic and clinical characteristics, non-white participants were nearly twice as likely not to have Medicare claims for depression among patients who met criteria for depression (“false negatives”). Smoking status, depression severity (HDRS), cardiovascular disease, and more primary care physician office visits were also significantly associated with decreased odds to be false negatives. In contrast, after covariate adjustment, white race and chronic pulmonary disease were associated with increased odds of a Medicare claim for depression among patients who did not meet criteria for depression (“false positives”). Using weights based on the screened sample, the positive predictive value of a Medicare claim for depression was 66% (95% CI [63%, 69%]), while the negative predictive value was 77% (95% CI [76%, 78%]). CONCLUSION: Investigators using Medicare data to study depression must recognize that diagnoses of depression from Medicare data may be biased by patient ethnicity and the presence of medical comorbidity.